A survey of DHT solutions in fixed and mobile networks. (2016) - Cherbal, Sarra; Boukerram, Abdellah; Boubetra, Abdelhak
Peer-to-peer (P2P) networks had experienced a great acceptance in recent years in the area of distributed computing, mainly attributed to their inherent management of some interests such as scaling, dynamic nature and heterogeneity that are required by the current network infrastructure. Specifically, structured P2P systems that have shown a great performance since their appearance due to the organisation they offer to the logical topology and objects placement according to specific algorithms. This survey presents a comprehensive and a critical study of research related to enhanced distributed hash tables (DHTs), by presenting a classification according to the used methods and a comparison based on some important points as the routing tables, maintenance cost, lookup process, etc. We discuss the strengths and the weaknesses of existing approaches, and then we highlight the research issues that still to be lacked in order to serve as a guide for interested researchers.